SOME ASPECTS OF BIOLOGY OF LAMBAK PIPIH FISH (Thynnichthys polylepis) IN BATANGHARI RIVER, JAMBI - Kaban, Siswanta (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2018)
Research on some biological aspects of lambak pipih fish (Thynnichthys polylepis) was carried out in the Batanghari River, Jambi Province. Using the survey method, in March, May, August and October 2015. The station was determined by purposive random sampling which was divided into 3 regions: upstream in Mangunjaya and Puntikalo Villages, Tebo Regency, the middle in Penyengat Kecil and Kunangan Villages, Jambi Municipality and downstream in Sungai Kandis and Muara Sabak Villages. The size of the flat-rolled fish caught ranges from 7.2 cm in length and weighs 4.5 grams and 26 cm in weight, 162 grams. The largest length is between 10.1 - 15.0 cm totaling 55 heads, while the most weight is 1 - 30 grams totaling 52 heads. The relationship between long-weight flatfish follows the equation pattern: W = 0.013L2.901 with a value of b <3. So it can be said that flat-slawed fish have a negative allometric growth pattern. Its natural feed consists of macrophytes (water growths) as much as 49.9% as the main feed. Phytoplankton supplementary feed is 22.6% (Chlorophyceae 10.4%; Bacillariophyceae 8.1% and Cyanophyceae 4.1%, and detritus 17.4%. Additional feed is 0.8% Protozoa; 0.5% Rotifera and Crustaceae 0 , 4% and the unidentified part was 8.4%. Thus flat or motak fish were classified into groups of herbivorous fish or plant eaters.